Oxygen isotope speedometry in granulite facies garnet recording fluid/melt–rock interaction (Sør Rondane Mountains, East Antarctica). (6th June 2019) - Higashino, Fumiko; Rubatto, Daniela; Kawakami, Tetsuo; Bouvier, Anne‐Sophie; Baumgartner, Lukas P.
Abstract: In situ analysis of a garnet porphyroblast from a granulite facies gneiss from Sør Rondane Mountains, East Antarctica, reveals discontinuous step‐wise zoning in phosphorus and large δ 18 O variations from the phosphorus‐rich core to the phosphorus‐poor rim. The gradually decreasing profile of oxygen isotope from the core (δ 18 O = ~15‰) to the rim (δ 18 O = ~11‰) suggests that the 18 O/ 16 O zoning was originally step‐wise, and modified by diffusion after the garnet rim formation at ~800°C and 0.8 GPa. Fitting of the 18 O/ 16 O data to the diffusion equation constrains a duration of the high‐ T event (~800°C) to c . 0.5–40 Ma after the garnet rim formation. The low δ 18 O value of the garnet rim, together with the previously reported low δ 18 O values in metacarbonates, indicates regional infiltration, probably along a detachment fault, of low δ 18 O fluid/melt possibly derived from meta‐mafic to ultramafic rocks.